Protein phosphatase 6 regulates mitotic spindle formation by controlling the T-loop phosphorylation state of Aurora A bound to its activator TPX2. - Zeng, K; Bastos, R; Barr, F; Gruneberg, U (2010)
Many protein kinases are activated by a conserved regulatory step involving T-loop phosphorylation. Although there is considerable focus on kinase activator proteins, the importance of specific T-loop phosphatases reversing kinase activation has been underappreciated. We find that the protein phosphatase 6 (PP6) holoenzyme is the major T-loop phosphatase for Aurora A, an essential mitotic kinase. Loss of PP6 function by depletion of catalytic or regulatory subunits interferes with spindle formation and chromosome alignment because of increased Aurora A activity. Aurora A T-loop phosphorylation and the stability of the Aurora A-TPX2 complex are increased in cells depleted of PP6 but not other phosphatases. Furthermore, purified PP6 acts as a T-loop phosphatase for Aurora A-TPX2 complexes in vitro, whereas catalytically inactive mutants cannot dephosphorylate Aurora A or rescue the PPP6C depletion phenotype. These results demonstrate a hitherto unappreciated role for PP6 as the T-loop phosphatase regulating Aurora A activity during spindle formation and suggest the general importance of this form of regulation.